Inclusão digital na biblioteca universitária: desenvolvimento de competência informacional nos usuários cegos e com baixa visão do Espaço Acessibilidade da BICEN - Santos, Anaise de Santana (2019)
This dissertation consists of a study developed within the Accessibility Space, a sector located in the central library of the Federal University of Sergipe, which involved blind users with low vision of the space problematizing their informational competence. These concepts were the basis of this research: digital inclusion, informational competence and information mediation. The objective was then to develop informational competence in blind and low vision users, emphasizing the mediating character of the professional librarian. The specific objectives were defined as follows: to identify existing digital inclusion and information competence development initiatives in the sector; verify the informational competence of blind and low vision users of the Accessibility Space; elaborate a printed manual in Braille to direct the use of the databases by blind and low vision users of the space. The data collection instruments used were open and semi-structured interviews. The analysis focused on the activities of digital inclusion and informational competence developed in the sector, as well as the level of informational competence of its users, under the parameters of: information needs, information sources, difficulties in access, obtaining information and use. of technology. The qualitative research method was considered the most appropriate for data analysis. It was found that the activities of digital inclusion and informational competence developed by the sector are at the initial level, access, it was observed that the need for information is linked to the courses taken by users and that knowledge of information sources is quite shallow on the part of these. . It is concluded that the Braille manual intended by this study was built which raises concerns about future research, thus proposing the investigation of how educational actions developed in the Accessibility Space can help the cognitive development of the visually impaired, as well as the development of information competence programs jointly by departmental teachers and the librarian.